(untitled) (Jurnal Teknologi (Sciences & Engineering), 2013)
Bacterial cellulose is a pure and highly hydrophilic material with high mechanical strength. Furthermore by adding certain substrates or by manipulating the operating conditions it is possible to change the properties of the bacterial cellulose. The objective of this research is to develop a modified method for fabrication of bacterial cellulose-polyaniline films. Polyaniline was incorporated into bacterial cellulose during fermentation by Acetobacter xylinum in order to produce conductive film. Bacterial cellulose/polyaniline film was synthesized with addition of polyaniline in Rotary-discs reactor during bacterial cellulose formation. The conductivity of film produced was measured and compared. The effects of polyaniline concentration were studied and the relationship between polyaniline concentration and film conductivity were determined.